2018
DOI: 10.1155/2018/4967318
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ferulate Attenuates Lidocaine‐Induced Corneal Endothelial Impairment

Abstract: The introduction of intracameral anaesthesia by injection of lidocaine has become popular in cataract surgery for its inherent potency, rapid onset, tissue penetration, and efficiency. However, intracameral lidocaine causes corneal thickening, opacification, and corneal endothelial cell loss. Herein, we investigated the effects of lidocaine combined with sodium ferulate, an antioxidant with antiapoptotic and anti-inflammatory properties, on lidocaine-induced damage of corneal endothelia with in vitro experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…All derivatives were characterized by high antioxidant activity, which was confirmed by other works on other FA derivatives. For example, it was found that sodium ferulate could protect human corneal endothelial cells from the oxidative damage induced by lidocaine, which causes corneal thickening, opacification, and corneal endothelial cell loss [ 51 ]. In another study a derivative of FA, hmy-paa (3-(4-hydroxy-3-methoxyphenyl)-N-(1H-pyrazol-3-yl) acrylamide), was demonstrated to selectively inhibit succinate dehydrogenase activity and efficiently abate myocardial cell injury caused by hypoxia [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…All derivatives were characterized by high antioxidant activity, which was confirmed by other works on other FA derivatives. For example, it was found that sodium ferulate could protect human corneal endothelial cells from the oxidative damage induced by lidocaine, which causes corneal thickening, opacification, and corneal endothelial cell loss [ 51 ]. In another study a derivative of FA, hmy-paa (3-(4-hydroxy-3-methoxyphenyl)-N-(1H-pyrazol-3-yl) acrylamide), was demonstrated to selectively inhibit succinate dehydrogenase activity and efficiently abate myocardial cell injury caused by hypoxia [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out on animal eyes determined that within six hours after death, the endothelium can be analysed without structural changes occurring in this layer (SIT et al, 2001;PIGATTO et al, 2005;PIGATTO et al, 2009;FAGANELLO et al, 2016). The use of slaughtered animal eyes for endothelial analysis has increasingly been shown to be an alternative to the use of live animals to assess the toxicity of intraocular drugs (PESCOSOLIDO et al, 2011;WEN et al, 2015;TERZARIOL et al, 2016;SILVA et al, 2018;JIANG et al, 2018). Corneal endothelial toxicity is related to substances that come into contact with the endothelium, based on their chemical compositions, pH and osmolarities (PARIKH & EDELHAUSER, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, scavenging ROS is beneficial to inhibiting the exacerbation of UC. Sodium ferulic (SF), one of the active ingredients in traditional Chinese medicine, is believed to be a potent ROS scavenger. According to previous studies, SF has shown promising potential in treating diseases such as neurodegenerative disorders, cardiovascular diseases, and cancer due to its powerful ROS-scavenging capacity. ,, However, the short in vivo half-life and low bioavailability restrict its further application . Incorporating SF into a CS-PDA hydrogel network can provide sufficient protection for SF and improve drug stability in vivo .…”
Section: Introductionmentioning
confidence: 99%